Changes in economic inequality in Europe and Latin America in the first decades of the twenty-first century - Salvia, Agustín (2021)
Fil: Salvia, Agustín. Pontificia Universidad Católica Argentina. Observatorio de la Deuda Social Argentina; Argentina